Microinjection Wound Assay and In vivo Localization of Epidermal Wound Response Reporters in Drosophila Embryos. - Juarez, Michelle T. (MyJove Corporation, 2013)
The Drosophila embryo develops a robust epidermal layer that serves both to protect the internal cells from a harsh external environment as well as to maintain cellular homeostasis. Puncture injury with glass needles provides a direct method to trigger a rapid epidermal wound response that activates wound transcriptional reporters, which can be visualized by a localized reporter signal in living embryos or larvae. Puncture or laser injury also provides signals that promote the recruitment of hemocytes to the wound site. Surprisingly, severe (through and through) puncture injury in late stage embryos only rarely disrupts normal embryonic development, as greater than 90% of such wounded embryos survive to adulthood when embryos are injected in an oil medium that minimizes immediate leakage of hemolymph from puncture sites. The wound procedure does require micromanipulation of the Drosophila embryos, including manual alignment of the embryos on agar plates and transfer of the aligned embryos to microscope slides. The Drosophila epidermal wound response assay provides a quick system to test the genetic requirements of a variety of biological functions that promote wound healing, as well as a way to screen for potential chemical compounds that promote wound healing. The short life cycle and easy culturing routine make Drosophila a powerful model organism. Drosophila clean wound healing appears to coordinate the epidermal regenerative response, with the innate immune response, in ways that are still under investigation, which provides an excellent system to find conserved regulatory mechanisms common to Drosophila and mammalian epidermal wounding.